A phosphatidylcholine hyaluronic acid chitin–nanofibrils complex for a fast skin remodeling and a rejuvenating look - Morganti P; Palombo P; Palombo M; Fabrizi G; Cardillo A; Svolacchia F; Guevara L; Mezzana P (Dove Medical Press, 2012)
Pierfrancesco Morganti,1 Paolo Palombo,2 Marco Palombo,3 Giuseppe Fabrizi,4 Antonio Cardillo,5 Fabiano Svolacchia,5 Luis Guevara,6 Paolo Mezzana71Department of Applied Cosmetic Dermatology, University of Naples Federico II, Naples, Italy; 2Department of Plastic, Reconstructive and Aesthetic Surgery, Saint Eugenio Hospital, Rome, Italy; 3Department of Plastic, Reconstructive and Aesthetic Surgery, CTO Hospital, Rome, Italy; 4Department of Dermatology, University of Parma, Parma, Italy; 5Centre of Nanoscience, Mavi Sud, Aprilia, Italy; 6Hospimedical, Pyrmont, Australia; 7IRCCS GB Bietti Eye Foundation, Rome, ItalyBackground: The reduction of mortality worldwide has led older individuals to seek intervention modalities to improve their appearance and reverse signs of aging.Objective: We formulated a medical device as innovative block-polymer nanoparticles based on phosphatidylcholine, hyaluronan, and chitin nanofibrils entrapping amino acids, vitamins, and melatonin.Methods: Viability and collagen synthesis were controlled on fibroblasts ex vivo culture while adenosine triphosphate production was evaluated on keratinocytes culture. Subjective and objective evaluations were performed in vivo on selected volunteer patients.Results: In accordance with our previous studies, both the in vitro and in vivo obtained results demonstrate the efficacy of the injected block-polymer nanoparticles in reducing skin wrinkling and ameliorating the signs of aging.Keywords: antiaging agent, scar correction, stretch marks, signaling molecules, photoaging, biostimulation